Data and Business Intelligence Systems for Competitive Advantage: prospects, challenges, and real-world applications - Djerdjouri, Mohamed (Mercados y Negocios, 2019)
This paper is intended as a short introduction to Business Intelligence and Analytics systems. The main aim of the paper is to raise awareness of organizations in the developing world, about the benefits of these technologies and the crucial role they play in the survival and competitiveness of the firm in the complex and turbulent global market. For many years, many small and medium-sized businesses (SMBs) have not followed large organizations in the implementation of Business Intelligence technologies. The main reason stated by SMBs is the complexity and high cost of deploying and managing BI systems. However, according to recent IT industry survey of SMBs executives, they now realize the crucial role BI systems play in the company’s performance, and competitiveness and they are now increasingly investing in and implementing Business Intelligence technologies.